(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Since the beginning of civilization numerous researchers, scholarly people connected with themselves in the undertaking of breaking down the idea of man and his association with his kindred creatures and with the general public in general. They saw and clarified human instinct in alternate point of view. Aristotle called man as a social and political creature. Criminology is the assemblage of information viewing crime as a social marvel. It incorporates inside its extension the way toward making laws, of overstepping laws and of responding towards infringing upon of laws. Criminology developed in the twentieth century as an interdisciplinary way to deal with the methodical investigation of crime, culprits and criminal conduct. In this Article, we studied about the female criminals and their Theories.